National Evaluation of Title I of the 1994 Crime Act: Survey Sampling Frame of Law Enforcement Agencies, 1993-1997 - Roth, Jeffrey ([Verlag nicht ermittelbar], 2001)
The data in this collection represent the sampling frame used to draw a national sample of law enforcement agencies. The sampling frame was a composite of law enforcement agencies in existence between June 1993 and June 1997 and was used in a subsequent study, a national evaluation of Title I of the 1994 Crime Act. The evaluation was undertaken to (1) measure differences between Community Oriented Policing Services (COPS) grantees and nongrantees at the time of application, (2) measure changes over time in grantee agencies, and (3) compare changes over time between grantees and nongrantees. The sampling frame was comprised of two components: (a) a grantee component consisting of agencies that had received funding during 1995, and (b) a nongrantee component consisting of agencies that appeared potentially eligible but remained unfunded through 1995.